Clinical Spectrum of Gynecological Disorder Among Hospitalized Adolescent : Study at Chittagong Medical College Hospital - Ferdous, Jannatul; Shirin, Fahmida; Bilkis, Afroza; Chowdhury, Muhammad Jabed Bin Amin; Begum, Mortuza; Banu, Nasreen (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Adolescent is one of the most challenging issues for health professionals. Today adolescent comprises 16% of world population, 50% of which are girl. To formulate disease pattern and to interfere related social factors ared time demanding. To address the gynaecological diseases pattern of adolescent girls (10-10 yrs) demanding admission in hospital. Materials and methods: This was an observational, descriptive study. All Adolescent girl admitted in Department of Obs & Gynae of Chittagong Medical College Hospital (CMCH) during November 2021-October 2022. Adoles- cent girls with obstetric comploications (>28 wks pregnan- cy) were excluded from this study. Results: A total of 68 adolscent girls ere evaluated in this study. They were classified as early teen (10-14 yrs, n=25, 36.76%) and late teen (15-19 yrs, n=43, 63.24%). Important socio demographic factors, married n=10, 14.71%, working n=5, 7.35%, student n=44, 84.70% and dropped out of school n=9, 13.24%. Of the girls, leading cause of hospitalization was ovarian tumor n=19, 27.94%. 2nd most reason for admission was menstrual disorder n=16, 23.52% and 3rd was malformation and maldevelopment of genital tract, n=12, 17.64%. Early pregnancy complications n=8, 11.76%, genital trauma n=5, 7.35% and others n=5, 7.35%. Conclusion: Diseases patten shows rising cases of ovarian tumor in adolescent and socio demographic factors like teenage marriage, school drop out needs to be addressed in improving adolescent care. JCMCTA 2023 ; 34 (2) : 125-127